The Effectiveness of The Blended–Kolb Experiential Learning Model in Improving Work Readiness in The Field of Fashion Technology - Fidia Kusniawati; Tri Joko Raharjo; Mintarsih Arbarini; Decky Avrilianda (Edutech Publishing Media, 2026)
Industry 5.0 requires vocational graduates to possess not only technical skills but also multidimensional work readiness. However, evidence regarding the integration of blended learning and experiential learning in vocational fashion technology training remains limited. This study examined the implementation of the Blended–Kolb Experiential Learning model and its association with trainees’ work readiness at BBPVP Semarang. A quantitative pre-experimental one-group pretest–posttest design was employed with 16 trainees. Data were collected through cognitive tests, psychomotor and affective observations, and a work-readiness questionnaire. The results showed improvements in cognitive (47.81–89.69), psychomotor (37.18–94.25), affective (33.00–91.75), and work-readiness scores (39.53–92.38). N-Gain values ranged from 0.81 to 0.91, while the paired-sample t-test indicated a significant difference between pretest and posttest scores (p < .001). The findings suggest that the model was associated with positive improvements in trainees’ competencies and work-readiness indicators. The study supports the integration of digital learning, experiential activities, reflection, and project-based practice in vocational education.